Transient Dynamics of Archaea and Bacteria in Sediments and Brine Across a Salinity Gradient in a Solar Saltern of Goa, India - Mani, Kabilan; Taib, Najwa; Hugoni, Mylène; Bronner, Gisele; Bragança, Judith M.; Debroas, Didier (Frontiers in Microbiology, 2020)
The microbial fluctuations along an increasing salinity gradient during two different salt production phases - initial salt harvesting (ISH) phase and peak salt harvesting (PSH) phase of Siridao solar salterns in Goa, India were examined through high-throughput sequencing of 16S rRNA genes. Elemental analysis of the brine samples showed the abundance of sodium (Na+) and chloride (Cl-) ions thereby indicating its thalassohaline nature. Comparison of relative abundance of sequences revealed that Archaea (34% to 91%) transited from sediment to brine while Bacteria (17% to 51%) transited from brine to sediment with increasing salinity. Incidence of Archaea was found to be significantly enriched even in low salinity and moderate salinity sediments with their relative sequence abundance reaching as high as 85%. Euryarchaeota was found to be the dominant archaeal phylum containing 19 and 17 genera in sediments and brine, respectively. Phylotypes belonging to Halorubrum, Haloarcula, Halorhabdus, and Haloplanus were common in both sediments and brine. Occurence of Halobacterium and Natronomonas were exclusive to sediments while Halonotius was exclusive to brine. Among sediments, relative sequence incidence of Halorubrum, and Halorhabdus decreased while Haloarcula, Haloplanus, and Natronomonas increased with increasing salinity. Similarly, the relative abundance of Haloarcula and Halorubrum increased with increasing salinity in brine. Sediments and brine samples harbored about 20 and 17 bacterial phyla, respectively. Bacteroidetes, Proteobacteria, and Chloroflexi were the common bacterial phyla in both sediments and brine while Firmicutes were dominant albeit in sediments alone. Further, Gammaproteobacteria, Alphaproteobacteria, and Deltaproteobacteria were observed to be the abundant class within the Proteobacteria. Among the bacterial genera, phylotypes belonging to Rubricoccus and Halomonas were widely detected in both brine and sediment while Thioalkalispira, Desulfovermiculus, and Marinobacter were selectively present in sediments alone. This study suggests that Bacteria are more susceptible to salinity fluctuations than Archaea, with many bacterial genera being compartment and phase-specific. Our study further indicated that Archaea rather than Bacteria could withstand the wide salinity fluctuation and attain a stable community structure within a short time-frame.